(untitled) (Marketing Journal, 2025)
This article highlights issues related to improving the planning of audits of employee settlements. In particular, it proposes a working paper for evaluating the internal control system related to employee settlements, a procedure for assessing internal co ntrol by elements, criteria for evaluating the reliability of internal control, a sample list of procedures for collecting audit evidence, as well as an audit plan and audit program.